2003
DOI: 10.1021/ma0217940
|View full text |Cite
|
Sign up to set email alerts
|

Dielectric Study on the Heterogeneous Dynamics of Miscible Polyisoprene/Poly(vinyl ethylene) Blends:  Estimation of the Relevant Length Scales for the Segmental Relaxation Dynamics

Abstract: Dielectric study was performed on the polyisoprene (PI)/poly(vinyl ethylene) (PVE) miscible blends. We observed the end-to-end vector fluctuation dynamics (normal mode) of PI as well as the two R-relaxation processes corresponding to the segmental motions of PVE and PI. Among these three relaxation modes, the normal mode relaxation behavior was examined in detail. Since this relaxation reflects the dynamics of the length corresponding to the end-to-end distance of PI chain, comparison of the relaxation times f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
95
0
3

Year Published

2004
2004
2015
2015

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 64 publications
(103 citation statements)
references
References 38 publications
5
95
0
3
Order By: Relevance
“…However, Alegria et al [2] found that miscible blends of cis-polyisoprene (PI) and poly(vinyl ethylene) (PVE) exhibit bimodal dielectric loss curves for the local segmental relaxation (a relaxation). Similar dielectric behavior was observed for polymer blends in which the difference of glass transition temperatures T g of the components is larger than 70 K [3][4][5][6][7][8][9][10]. Hereafter the term 'bimodal' means that a loss curve clearly exhibits two peaks or a main peak and a shoulder.…”
Section: Introductionsupporting
confidence: 67%
See 3 more Smart Citations
“…However, Alegria et al [2] found that miscible blends of cis-polyisoprene (PI) and poly(vinyl ethylene) (PVE) exhibit bimodal dielectric loss curves for the local segmental relaxation (a relaxation). Similar dielectric behavior was observed for polymer blends in which the difference of glass transition temperatures T g of the components is larger than 70 K [3][4][5][6][7][8][9][10]. Hereafter the term 'bimodal' means that a loss curve clearly exhibits two peaks or a main peak and a shoulder.…”
Section: Introductionsupporting
confidence: 67%
“…Fig. 8 shows the plots of logðf ms =f 0 ms Þ versus DT g for blends of polyethers examined in this study and those reported so far [5,8,9]. It is noted that the blends reported in Refs.…”
Section: Resolution Of the Segmental Relaxationmentioning
confidence: 61%
See 2 more Smart Citations
“…Extensive studies have been conducted for such miscible blends to examine the dynamics of monomeric segments being related to the glass transition. [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15] Those studies revealed characteristic features of the miscible blends such as the broad (almost two-step) glass transition noted in thermal measurements, the broad modes of segmental motion detected with NMR, and the broad and thermo-rheologically complex relaxation processes observed with the dielectric/viscoelastic methods. These features are related to the self-concentration effect 16 and the local composition fluctuation.…”
Section: Introductionmentioning
confidence: 98%